SCIENTIFIC APPROACH BASED TRANSLATION USED BY EFL JUNIOR HIGH SCHOOL TEACHER - Sumarningsih N.M.; Batan I Gede; Adnyani L.D.S. (Lingua Scientia, 2018)
This study was conducted as an attempt to investigate in what step of scientific approach the teachers most frequently use translation in English Language Teaching as well as to find out the teachers’ reasons toward the use of translation in English Language Teaching based on scientific approach at SMP Negeri 4 Singaraja and SMP Negeri 5 Singaraja. It was conducted in qualitative research design. There were two teachers chosen as the subjects of study. The data were collected through audio recording the teaching and learning process and interviewing the subjects of study, while the techniques of analyzing data were done descriptively following the four processes according to the theory of Miles & Huberman (1984), namely: data collection, data reduction, data display, and conclusion drawing. The results of analysis indicated that the teachers most frequently used translation in exploring step of scientific approach. In addition, there were seven teachers’ reasons found in relation to the use of translation in the classroom, namely to help the students’ difficulty in: (1) understanding the instruction given by the teacher, (2) understanding the English vocabulary, (3) asking something in English, (4) understanding the tenses or grammar, (5) understanding the material deeply, (6) doing the task, and (7) presenting their work. The related parties interested in the same area of the research should give deeper concern in doing wider range of aspects involved in further study.